Biomarker gradients of super-viscous oil as an estimation method of oil-water distribution. Issue 5 (3rd September 2019) - Chemodanov, Artem; Sudakov, Vladislav; Khayrtdinov, Rinat; Safina, Regina
ABSTRACT: In this article, we consider a promising method for estimating the water saturation of a super-viscous oilfield (hereinafter, SVO field) in the case of Cheremshansky oilfield, Russian Federation. A lithological description of the reservoir was carried out and gas chromatography-massspectrometry analysis of hydrocarbon fractions of core bitumoid was performed. It is shown that the ratios of certain biomarkers (methyldibenzothiophenes, 6H-Farnesol and pristane) SVO have extrema, both at the end of oil reservoir, and in the middle. Based on the fact that such dependencies indirectly indicate the distribution of water in the oil reservoir, the authors formulated the conclusion that there is no pure water reservoir (along the studied wells). Also, the authors have shown that the distribution of the 'oil-water' by measuring the gradients of concentrations of biomarkers SVO bears certain advantages and is a good addition to the classic geophysical methods.